DETERMINATION OF PHYSICAL ACTIVITY PARTICIPATION STATUS OF PRIMARY SCHOOL STUDENTS - Karadag, Mustafa (Centro Univ la Salle-Rj, 2024)
This research was conducted to determine the level of participation in physical activity of primary school students. The research group consists of 236 (120 male, 116 female) volunteer students studying at primary school in the province of Elazig in the 2022-2023 academic year. In the research, Personal Information Form and Motivation for Participation in Physical Activity Scale (FAKMO) to determine students' participation in physical activity were used as data collection tools. The data were analyzed using the SPSS statistical package program. Significance was accepted as p<0.05. It was observed that the research group's total score average of the students' motivation to participate in physical activity scale was at a high level with 57.01 +/- 4.76, and there was a significant difference between the gender variable and the total mean score of the motivation scale of participation in physical activity (p>0.05). It was determined that male students had a higher average score in terms of participation in physical activity. It was seen that there was no significant difference between the participants' sports status, height, body weight, perceived income status and weekly physical exercise status and the motivation scale for participation in physical activity. It has been determined that the students who regularly do sports in the research group have higher motivation levels to participate in physical activity. It was determined that there was a significant and negative relationship between the gender of the participants and the motivation scale of participation in physical activity. In conclusion; It was seen that the students in the research group had a high level of participation in physical activity and there was a negative relationship between gender and participation in physical activity.
Keywords: Primary Education; Physical Activity; Student; Exercise